Long-Term Functional Ability Trajectories and Mental Health Among Older People Before and After the Covid-19 Pandemic Onset in Chile - Villalobos-Dintrans, P (Routledge, 2023)
Objectives: Despite the advances in understanding the complex association between functional abilities and mental health in old age, studies have overlooked two important aspects. First, traditionally, research has employed cross-sectional designs, measuring limitations at a single time point. Second, most gerontological studies on this field have been conducted before the COVID-19 pandemic onset. This study aims to explore the association between diverse long-term functional ability trajectories across late adulthood and old age, and older people’s mental health in Chile, before and after the COVID-19 pandemic onset. Methods: We use data from the population-representative and longitudinal ‘Chilean Social Protection Survey’, sequence analysis to reconstruct functional ability trajectory types from 2004 to 2018, and bivariate and multivariate analyses to measure their association with depressive symptoms in early 2020 (N = 891) and late 2020 (N = 672). We analyzed four age groups defined by their age at baseline (2004): people aged 46–50, 51–55, 56–60, and 61–65. Results: Our findings indicate that erratic or equivocal patterns of functional limitations across time (with people transiting back and forth between low and high levels of limitations) show the worst mental health outcomes, both before and after the pandemic onset. Prevalence of people with depression increased after the COVID-19 onset in most groups, being particularly high among those with previous equivocal functional ability trajectories. Conclusions: The relationship between functional ability trajectories and mental health calls for a new paradigm, moving away from age as the main policy guide, and highlighting the need to adopt strategies to improve population-level functional status as an efficient policy to address the challenges of population aging. © 2023 Informa UK Limited, trading as Taylor & Francis Group.